Anticipating the Emerging of Some Strategical Infectious Animal Diseases in Indonesia Related to The Effect of Global Warming and Climate Change - Sjamsul Bahri; T Syafriati (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2011)
The effect of global warming and climate change is changing the season, included flooding in one area and very dry in other area, changing the temperature and humidity. These changes will trigger changing of the life of biological agent (virus, bacteria, parasites and so on), variety of animal species, variety of vectors as reservoir host of animal with the role of transmitting the disease to other animal species, This condition will trigger the new animal disease (emerging disease) or old disease will be re-emerged (re-emerging diseases). This paper will discuss the effect of global warming and climate change on animal diseases in Indonesia such as Bluetongue (BT), Nipah, Japanese encephalitis (JE), West Nile (WN), and Rift Valley fever (RVF). The climate changes such as increasing the earth temperature and rainfall will cause extremely increase of vector population for BT, JE, WN and RVF. In addition, animal transportation and bird migration from one country to others or region will cause changing of ecological system and will open the chance to distribute the diseases. Hence, anticipation on those disease outbreaks should be taken by conducting the surveilance and early detection to those diseases. The possibility of entering Nipah disease in Indonesia should be anticipated because the avaibility of Nipah virus and the reservoir host (Pteropus spp) and also pigs as amplifier host in the surrounding area. Other diseases such as, leptospirosis, anthrax and avian influenza (H5N1) are also have a wider potential to distributing the disease related to the climate change in Indonesia. Key words: Global warming, climate change, zoonotic disease